Optimasi pH dan Konsentrasi Elektrolit dalam Elektrokoagulasi Limbah Surfaktan - Hanumi Oktiyani Rusdi; Surjani Wonorahardjo; Yudhi Utomo; Anugrah Ricky Wijaya (State University of Malang or Universitas Negeri Malang (UM), 2020)
Surfactants are organic materials that act as active ingredients in detergents, soaps and shampoos which can reduce the surface tension of the water so that the particles attached to the materials being washed are released and float or dissolved in water thus polluting the environment. Therefor it is necessary to separate or change them into other harmless materials before being discharged into the environment. One of the methods used is electrocoagulation. The electrocoagulation method is an environmentally friendly method of treating liquid waste by combining the principles of coagulation, flotation and electrochemistry. In this study, the electrocoagulation method was carried out by varying pH and electrolyte concentrations in the simulated surfactant waste treatment. Surfactant levels were determined by spectrophotometer in methylene blue. The optimization of the method is done by determining the maximum absorption length, optimum pH, and the effect of adding electrolytes with different concentrations. The results showed that the maximum absorption at a wavelength of 659 nm. The electrocoagulation process runs optimally at pH 2 with the addition of 7mM Na2SO4 electrolyte resulting in a% removal of 65%.